4x +y/3 = 8/3; x/2 +3/4y = -5/2 Solve the pair of linear equation by substitution method .find x and y
Answers
Answered by
172
Hi ,
4x + y/3 = 8/3
multiply each term with 3 , we get
12x + y = 8
=> y = 8 - 12x ---( 1 )
x/2 + 3y/4 = -5/2----( 2 )
Substitute y = 8 - 12x in equation ( 2 ),
x/2 + ( 3/4 )[ 8 - 12x ] = -5/2
=> x/2 + 3[ 8/4 - 12x/4 ] = -5/2
=> x/2 + 3( 2 - 3x ) = -5/2
multiply each term with 2 , we get
=> x + 6( 2 - 3x ) = -5
=> x + 12 - 18x = -5
=> -17x = -5 - 12
=> -17x = -17
=> x = ( -17 )/( -17 )
x = 1
put x = 1 , in equation ( 1 ) , we get
y = 8 - 12 × 1
y = 8 - 12
y = -4
Therefore ,
x = 1 , y = -4
I hope this helps you.
; )
4x + y/3 = 8/3
multiply each term with 3 , we get
12x + y = 8
=> y = 8 - 12x ---( 1 )
x/2 + 3y/4 = -5/2----( 2 )
Substitute y = 8 - 12x in equation ( 2 ),
x/2 + ( 3/4 )[ 8 - 12x ] = -5/2
=> x/2 + 3[ 8/4 - 12x/4 ] = -5/2
=> x/2 + 3( 2 - 3x ) = -5/2
multiply each term with 2 , we get
=> x + 6( 2 - 3x ) = -5
=> x + 12 - 18x = -5
=> -17x = -5 - 12
=> -17x = -17
=> x = ( -17 )/( -17 )
x = 1
put x = 1 , in equation ( 1 ) , we get
y = 8 - 12 × 1
y = 8 - 12
y = -4
Therefore ,
x = 1 , y = -4
I hope this helps you.
; )
zubair09:
thanks
Answered by
34
Answer:
Step-by-step explanation:
=》 4x+y/3=8/3
Multiply by 3
so, we get,
=12x+y=8
= y=8-12x –––– 1
And
= x/2+3y/4= -5/2 -------2
Now put the value of y in eq-1
=》 x/2+(3/4)(8-12x)=-5/2
=》x/2+3(8/4-12x/4)=-5/2
=》x/2+3(2-3x)=-5/2
multiply each term by 2
=》x+6(2-3x)=-5
=》x+12-18x=-5
=》-17x=-17
=》x=1
Putting x=1 in equation-----1
Y=8-12×1
Y=-4
X=1 and Y=-4
Similar questions